Content Analysis Of Instagram Account @Ykesperempuan As An Educational And Campaign Medium For Adolescent Sexual and Reproductive Health - Sulistyarini, Dhanik; Sugiyanta, Sugiyanta (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to analyze the content of the @ykesperempuan Instagram account as an educational and campaign medium for adolescent sexual and reproductive health. This research used content analysis by grouping the information displayed in theme categories, the format of the content displayed, and analyzing the engagement of the followers. The results showed that there were five categories of themes on the @ykesperempuan Instagram account. These are education, information on activities, campaigns, national/international holidays, and others. There were some formats of the content, such as photo and text information, infographics and text, video and text, and podcasts. Follower engagement on the @ykesperempuan account is still low because only 12.5% ​​of all posts receive active responses in the form of comments, and most of the followers' responses are passive responses (likes). Based on these results, it is recommended that the @ykesperempuan account use more content with audio-visual formats, both in the form of videos and podcasts to attract more audiences, so that they can disseminate information and campaigns to a wider audience. In addition, the use of photos and videos can also be done to increase follower engagement on @ykesperempuan account.